Endocarditis Caused by Extended-Spectrum-β-Lactamase-Producing Klebsiella pneumoniae: Emergence of Resistance to Ciprofloxacin and Piperacillin-Tazobactam during Treatment despite Initial Susceptibility - Zimhony, Oren (American Society for Microbiology, 2006)
Three episodes of bacteremia occurred in the course of prosthetic valve endocarditis caused by an extended-spectrum-β-lactamase (ESBL)-producing Klebsiella pneumoniae strain. The second isolate developed resistance to ciprofloxacin and the third isolate to piperacillin-tazobactam (PIP-TZ) following sequential therapy with each agent. The first isolate was resistant to PIP-TZ only at high inocula, the second isolate acquired increased transcription of the acrA gene, and the third isolate became resistant to PIP-TZ due to loss of β-lactamase inhibition by TZ. We question if and how PIP-TZ susceptibility should be reported for ESBL-producing Enterobacteriaceae.